Confessional diplomacy in early modern Europe - Anderson, Roberta; Backerra, Charlotte (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Confessional Diplomacy in Early Modern Europe examines the role of religion in diplomacy in early modern Europe. In the period following the Reformations, Europe became divided: all over the continent princes and their people segregated over theological, liturgical, and spiritual matters. At the same time, diplomacy rose as a means of communication and policy, so all powers established long- or short-term embassies and sent envoys to other courts and capitals. The book addresses three main areas where questions of religion and/or confession played a role: Papal diplomacy, priests and other clerics as diplomatic agents, and religion as a question for diplomatic debate, especially concerning embassy chapels"--
OCLC-licensed vendor bibliographic record.
Keywords: Catholic Church -- Foreign relations -- Europe -- History; Diplomacy -- Religious aspects -- Catholic Church -- History; Diplomacy -- Religious aspects -- Christianity -- History; Diplomacy -- History; Christianity and international relations -- Europe -- History; HISTORY / General